Синтез оптимальних керуючих впливів двоконтурної сак режимами плавлення в дсп за електротехнологічними критеріями - Паранчук, Роман Ярославович (НТУ "ХПІ", 2010)
Electro-technology suitability of melting modes optimization in arc steel-melting furnace based on criterion of maximum lining irradiation coefficient and maximum metal heating coefficient was substantiated. Mathematical models of synthesis of optimal arc voltage setting for given artificial external furnace characteristics, which are formed by two-contour melting modes control system, was worked out. Adaptation of optimal control to change of arc voltages dispersion is proposed, which is implemented on basis of fuzzy regulator.
Synthesis of two-contour control system optimal influences for regulating melting modes in arc steel-melting furnace based on electro-technology criterion
Keywords: піч сталеплавильна; піч дугова; керування автоматичне; модель математична; продуктивність; потужність